Peningkatan pengetahuan tentang Perilaku Hidup Bersih dan Sehat (PHBS) pada santri Pondok Pesantren Tahfidzul Qur’an Hidayatullah Kota Ternate - Mutmainnah, Mutmainnah; Sibadu, Muhammad Subhan A. (Universitas Mataram, 2025)
This study aims to enhance the knowledge of students at Pondok Pesantren Tahfidzul Qur’an Hidayatullah Ternate regarding Perilaku Hidup Bersih dan Sehat (PHBS) through educational activities. As an Islamic educational institution, pesantrens often face health issues that can be mitigated by implementing PHBS. The study employed lecture and discussion methods to provide PHBS education to junior high school students. Evaluation was conducted using pre-test and post-test questionnaires, revealing a significant improvement in students' knowledge. Statistical analysis showed that the average knowledge score increased from 57 ± 19.49 in the pre-test to 80.5 ± 14.31 in the post-test, with a significance value of p < 0.000. The activity also included the establishment of a Health Post for Pesantren (Poskestren) to support the implementation of PHBS. The conclusion of this study is that the conducted education effectively improved students' knowledge of PHBS, which can contribute to better health within the pesantren environment. This educational program is expected to be implemented in other pesantrens to expand the health benefits among students.